Severe hypothyroidism‐induced rhabdomyolysis: A case report - Mohamed Abdunasser Baghi (14777836) (2023)
Hypothyroidism causing rhabdomyolysis is a known but an uncommon entity. Hashimoto's thyroiditis causing rhabdomyolysis in the absence of precipitating factors is even rarer. Here, we report a 42-year-old previously healthy man with hypothyroidism due to Hashimoto's thyroiditis complicated by severe rhabdomyolysis and acute kidney injury in the absence of precipitating factors. The diagnosis was based on his clinical presentation and laboratory investigations, and he was successfully treated with intravenous fluid therapy and oral levothyroxine. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.5107